2019
DOI: 10.1007/s00432-019-03039-2
|View full text |Cite
|
Sign up to set email alerts
|

“Risk of de novo or secondary cancer after solid organ or allogeneic haematopoietic stem cell transplantation”

Abstract: Solid organ (SOT) and allogeneic haematopoietic stem cell (HSCT) transplant recipients have elevated risk of de novo or secondary cancers. We explored risk factors hereof. Methods Among SOT and HSCT transplanted between January 2004-December 2014, standardized incidence ratio (SIR) of de novo/secondary cancer compared with the Danish population was determined and risk factors identified using Poisson regression. Results During a median of 3.4 (IQR 1.3-6.4) and 2.6 (0.8-5.4) person-years (PY) after SOT and HSCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
3
0
3
Order By: Relevance
“…Supplementary Table S3 provides details of the included studies, which involved e1848068-2 a total of 2,105,122 solid organ transplant recipients and reported 45 types of site-specific cancer. Of them, 52 studies 7,8,75 provided SIRs of multiple cancers of solid organ transplantations (11 for multiple organs, 7,8,[17][18][19][20][21][22][23][24][25] 19 for kidney, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] 16 for liver, [45][46][47][48][49][50][51][52][53][54][55]75 7 for heart and/or lung [60][61][62][76]…”
Section: Systematic Search and Study Characteristicsmentioning
confidence: 99%
“…Supplementary Table S3 provides details of the included studies, which involved e1848068-2 a total of 2,105,122 solid organ transplant recipients and reported 45 types of site-specific cancer. Of them, 52 studies 7,8,75 provided SIRs of multiple cancers of solid organ transplantations (11 for multiple organs, 7,8,[17][18][19][20][21][22][23][24][25] 19 for kidney, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] 16 for liver, [45][46][47][48][49][50][51][52][53][54][55]75 7 for heart and/or lung [60][61][62][76]…”
Section: Systematic Search and Study Characteristicsmentioning
confidence: 99%
“…However, very few data are available on the role of aberrant immune activation in the complex process of cancerogenesis occurring in liver transplanted patients. A previous study suggested no difference in the expression of activated CD8 + CD38 + T cells between patients who developed malignancies and non-cancer patients ( 29 ), but in a Danish cohort of solid organ transplant recipients, older age and elevated levels of C-reactive protein, a circulating marker of inflammation, correlated with a high risk for cancer development ( 30 ). In this study, levels of 16S rDNA and mtDNA, markers of PAMPs and DAMPs respectively, were higher at baseline in LT-PTM than in LT-no-PTM patients and remained higher at tumor onset.…”
Section: Discussionmentioning
confidence: 99%
“…Начиная с первых трансплантаций донорских органов был отмечен повышенный риск развития рака различных локализаций у реципиентов солидных органов [1,2,[6][7][8][9][10]. Большинство авторов приходят к заключению, что в течение следующего десятилетия злокачественные новообразования станут ведущей причиной смерти у реципиентов солидных органов [3,4,[11][12][13].…”
Section: эпидемиологияunclassified
“…С учетом неуклонно возрастающего количества трансплантаций солидных органов во всем мире (только за 2020 год в мире выполнено 113 363 трансплантации солидных органов) и постепенного увеличения продолжительности жизни реципиентов донорских органов актуальность изучения злокачественных новообразований будет только возрастать. Вопросы развития онкозаболеваний у этой категории достаточно подробно освещены в иностранной литературе, тогда как отечественных источников мы не нашли [1][2][3][4][5][6][7][8][9][10][11][12][13]30].…”
Section: Introductionunclassified